(untitled) (International journal of artificial intelligence, 2026)
Chronic placental insufficiency (CPI) remains a critical obstetric complication, serving as a primary vector for intrauterine growth restriction, preterm birth, and perinatal mortality. In regions experiencing severe ecological degradation, such as the Republic of Karakalpakstan in the Aral Sea disaster zone, the etiology of CPI is profoundly compounded by environmental toxicity, high regional rates of maternal anemia, and the prevalent transmission of congenital (TORCH) infections. This comprehensive report investigates the synergistic impact of environmental factors and infectious agents on the pathomorphological and immunohistochemical (IHC) architecture of the human placenta. Utilizing advanced digital histomorphometry and computational image analysis, the study quantifies key biomarkers associated with angiogenesis (VEGF), cellular proliferation (Ki-67), apoptosis (Caspase-3), and localized inflammatory responses (CD68).